The Asymmetric Impacts of Fiscal Consolidation on Poverty and Social Exclusion: Regional Perspective - Pošta, Vít (REGION, 2022)
The presented paper contributes to the current state of discussion about the effects of fiscal policy on economic activity in three key points. It focuses on the effects of fiscal policy on poverty and social exclusion instead of on broad measures of economic performance, the analysis is performed on the regional level of some EU national economies and it focuses on possible asymmetric impacts according to the level of the economic performance of the regions regarding the national levels. The results show that fiscal restrictions, both expenditure and income-oriented, have significant negative impacts on both poverty and social exclusion. Especially as far as social exclusion is concerned the impacts on the already underperforming regions seem to be even more profound. When poverty is considered as a measure of inequality instead of social exclusion then revenue-oriented fiscal restrictions seem relatively more harmful than expenditure-oriented fiscal consolidations as far as the underperforming regions are concerned.